PRODUKSI UMBI MINI (G0) KENTANG DARI STEK MINI DALAM RUMAH KETAT SERANGGA - Anton Gunarto (Jurnal Matematika Sains dan Teknologi, 2005)
The purpose of the research is to apply the cultivation technology in mini tuber (G0) and to investigate the phenotypic performances quantitative of three potato clones A5, PAS3063 and PAS3064 which were resistant from bacterial wilt disease (Ralstonia solanacearum). The commercial potato varieties (Granola and Atlantic) were used as comparison varieties. All clones (A5, PAS3063 and PAS3064), and two other varieties (Granola and Atlantic) wereconsistently resistant from bacterial wilt disease. The vegetative and the production variables of the tested clones were significantly different from those two commercial potato varieties. A5 and PAS3064 clones showed better vegetative and production characteristic than two commercial potato varieties. PAS3064 clone showed better performance compared with Atlantic variety, but it was almost similar compare with Granola variety.